The Study of Cultural Identity to Promote Community Based Tourism of Bang Luang Market, Nakhonpathom province - ช้ำเกตุ, กานต์นภัส (RMUTL Journal of Socially Engaged Scholarship, 2024)
Cultural tourism is essential to the state's policy for stimulating the economy and generating income for communities. Thailand boasts a rich and enduring cultural heritage, with diverse aspects that render each tourist destination unique. Nevertheless, similarities exist in the Thai way of life and culture. Creating a tourism identity that reflects the essence of the local community and captures tourists' interest is crucial for attracting visitors. This research focused on studying and gathering cultural information about the Bang Luang Market community in Nakhon Pathom province, conducting in-depth interviews with a specific sample group of 10 individuals considered traditional residents of the area. This aimed to reflect the cultural heritage of the community, and the research results found that old wooden houses, the Tuptim Goddess Shrine, ancient Chinese musical instruments, the annual Chinese New Year procession, local cuisine (Chun Pia), and Chinese musical performances are elements that define the community's identity. These findings can be used to enhance and promote tourism in various ways. For example, creating training programs related to local cuisine and Chinese music can help strengthen and sustain the community's future.